Sema3a plays a role in the pathogenesis of CHARGE syndrome. (8th February 2018) - Ufartes, Roser; Schwenty-Lara, Janina; Freese, Luisa; Neuhofer, Christiane; Möller, Janika; Wehner, Peter; van Ravenswaaij-Arts, Conny M A; Wong, Monica T Y; Schanze, Ina; Tzschach, Andreas; Bartsch, Oliver; Borchers, Annette; et al.
Abstract: CHARGE syndrome is an autosomal dominant malformation disorder caused by heterozygous loss of function mutations in the chromatin remodeler CHD7 . Chd7 regulates the expression of Sema3a, which also contributes to the pathogenesis of Kallmann syndrome, a heterogeneous condition with the typical features hypogonadotropic hypogonadism and an impaired sense of smell. Both features are common in CHARGE syndrome suggesting that SEMA3A may provide a genetic link between these syndromes. Indeed, we find evidence that SEMA3A plays a role in the pathogenesis of CHARGE syndrome. First, Chd7 is enriched at the Sema3a promotor in neural crest cells and loss of function of Chd7 inhibits Sema3a expression. Second, using a Xenopus CHARGE model, we show that human SEMA3A rescues Chd7 loss of function. Third, to elucidate if SEMA3A mutations in addition to CHD7 mutations also contribute to the severity of the CHARGE phenotype, we screened 31 CHD7 -positive patients and identified one patient with a heterozygous non-synonymous SEMA3A variant, c.2002A>G (p.I668V). By analyzing protein expression and processing, we did not observe any differences of the p.I668V variant compared with wild-type SEMA3A, while a pathogenic SEMA3A variant p.R66W recently described in a patient with Kallmann syndrome did affect protein secretion. Furthermore, the p.I668V variant, but not the pathogenic p.R66W variant, rescues Chd7 loss of function in Xenopus, indicating that the p.I668V variant is likely benign. Thus, SEMA3A is part of an epigenetic loop that plays a role in the pathogenesis of CHARGE syndrome, however, it seems not to act as a common direct modifier.